A SYNERGISTIC STRATEGY FOR MIS CURRICULUM DEVELOPMENT: RESPONSE TO RAPIDLY ADVANCING INFORMATION TECHNOLOGY. - Desai, Mayur S.; Von Der Embse, Thomas (College Student Journal, 2001)
Training and education of Information Systems (IS) professionals by both business organizations and educational institutions are critical in the pervasive Information Technology (IT) advances and utilization by end users. Due to rapid changes in IT, educational institutions have to constantly upgrade their training for providing appropriate education to their graduating students who along with their employers will be the end users of IT. It also makes these students more marketable in the competitive environment. The present strategy of MIS curricula seems to be broad and focuses more on concepts versus specific IT tools. This study addresses key issues with the existing strategies and proposes a synergistic approach to MIS curriculum development to augment the current strategies. A synergistic approach calls for a four-way partnership between Information Systems faculty, software developers, business and education faculty, and corporate management. The proposed strategy is based on a technique similar to integrated IT planning in organizations suggested by several researchers.